Development of Web Based Secret Snake Ladder Media for Learning to Make Simple Mandarin Sentence - Widuri, Ananda Wahyu Puspa; Pratita, Ina Ika; Amri, Miftachul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Mandarin is increasingly significant in the global and bilateral context between Indonesia and China. However, students often face challenges in mastering basic vocabulary essential for forming simple sentences. This study aims to develop an interactive web-based learning media called "Secret Snake Ladder" to support Mandarin vocabulary learning for 11th-grade students. The media was designed using the 4-D development model (Define, Design, Develop, Disseminate) and validated by experts in media, content, and language. Validation results indicate that the media is highly feasible for use, with an average score of 100%. Trials with students showed positive responses, achieving an effectiveness rate of 98%. This media not only enhances vocabulary acquisition but also motivates students through interactive gamification. With its accessibility and flexibility, Secret Snake Ladder serves as a modern and relevant solution for Mandarin language learning in the digital era.